Exploring variation of influences of caste and ethnicity in rural mountain household food security in Nepal - Chuwan, Nar Kumar (BARUN Journal, 2024)
This study investigates the impact of caste and ethnicity on household food security in Makalu Rural Municipality, a rural mountainous area in Nepal characterized by its diverse ethnic composition and reliance on subsistence agriculture. Employing a cross-sectional household survey methodology, data were collected from 262 households using the Household Food Insecurity Access Scale to measure food security levels. The study reveals significant variations in food security across different caste and ethnicity, with Sherpa households exhibiting the highest levels of food insecurity. These disparities are influenced by socio-economic factors closely linked to the caste and ethnicity system, which restricts access to resources and opportunities. Findings are interpreted through the lens of human capital theory and entitlement theory, emphasizing the role of social and economic entitlements in securing food. The study concludes with recommendations for policy interventions that address both the economic and socio-cultural dimensions of food insecurity. The implications of this research are critical for designing targeted strategies that enhance food security in rural Nepal, particularly by addressing caste and ethnicity-based disparities.